Report of the International Stem Cell Banking Initiative Workshop Activity: Current Hurdles and Progress in Seed‐Stock Banking of Human Pluripotent Stem Cells. (24th October 2017) - Kim, Jung‐Hyun; Kurtz, Andreas; Yuan, Bao‐Zhu; Zeng, Fanyi; Lomax, Geoff; Loring, Jeanne F.; Crook, Jeremy; Ju, Ji Hyeon; Clarke, Laura; Inamdar, Maneesha S.; Pera, Martin; Firpo, Meri T.; et al.
Abstract: This article summarizes the recent activity of the International Stem Cell Banking Initiative (ISCBI) held at the California Institute for Regenerative Medicine (CIRM) in California (June 26, 2016) and the Korean National Institutes for Health in Korea (October 19–20, 2016). Through the workshops, ISCBI is endeavoring to support a new paradigm for human medicine using pluripotent stem cells (hPSC) for cell therapies. Priority considerations for ISCBI include ensuring the safety and efficacy of a final cell therapy product and quality assured source materials, such as stem cells and primary donor cells. To these ends, ISCBI aims to promote global harmonization on quality and safety control of stem cells for research and the development of starting materials for cell therapies, with regular workshops involving hPSC banking centers, biologists, and regulatory bodies. Here, we provide a brief overview of two such recent activities, with summaries of key issues raised. Stem Cells Translational Medicine 2017;6:1956–1962 Abstract : This article reviews recent discussions among world leading groups working on provision of stem cell lines for research and clinical use. ISCBI confirmed the need for standards of quality control, safety, ethics, and resource sharing.